(3aj GdMLQs - (3GdeUQj, YHO GdNGdbs ((3HdOI SdGfjcs)
(3ChdgG (B:s
(3HSe Gddg aUd aj GdMLQ GdMb hGNJdGa CfhGYg bGd GYde CjgG GdCN GdcQje habc Gddg dWGYJg Cf GdCedGM hEf cGfJ LfSG hGMOG JQLY Edi fhYjf ZHGjW heSJNQLI hGdZHGjW JQLY Edi s
(3BNQgG (B:s
(3hcd Pdc jTjQ Edi MLQ hGMO hWHjYI hGMOg jbhe cd eG hLO efgG MGVQG HJOHjQ hGMO hgh GdQeR GdeJab Ydjg EP GdeSJNQL efgG bO QLY HGdGSJNQGL Edi CUd WHjYI GdChdi GdZHjWI Je HMeO Gddgs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdcjejGA hGdWHjYjGJs